EFEKTIFITAS ANTIKANKER FRAKSI (Curcuma zedoaria) DAN PENGARUHNYA TERHADAP EKSPRESI GEN CASPASE 3 PADA SEL HELA SECARA IN VITRO - Sumantri, Apria Wilinda (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2018)
Aim : The purpose of this research was the evaluate the efficacy of anti-cancer of active fraction of temu putih (Curcuma zedoaria) and their effects on expressetion caspase 3 in Hela cells in vitro Method: Do experimental study in Vitro the research population was whie the Hell cell meanwhile the research sample was HeLa cell that grow normally in cell number of 1 x 104 cell/well. The treatment group was ethanolextract, n-hexane fraction, ethyl acetatefraction and ethanol-water fraction of temu putih (Curcuma zedoaria ) were divided into 6 concentrations, that is 1000, 500, 250, 125, 62,5 dan 31,25 ug/ml; I negative control group ; and the positive control group of cispilatin with a concentration of 200, 100, 50, 25, 12,5 dan 6,25 ug/ml. the data were analyze SPSS Version 20. Result: The research findings showed that the n-hexane fraction of temu putih (Curcuma zedoaria) with the concentration of 154,261 ug/ml has the ability to induce apoptosis of 42.34% and increased the expression of caspase 3of 29,44% in Hell cells. Where as the IC50  Valuve of 20,823 ug/ml. Conclusion :       I can be said that the n-hexane fraction has the equivalent ability tp cisplatin 200 mg/ml in inhibiting growth and its effect on the expression of caspase 3 in HeLa cells In Vitro Keywords : N-hexane fraction, Temu putih (Curcuma zedoaria), anti-cancer, HeLa cells, Caspase 3